Notes on the Eskimo Kayak - Mercanton, P. L. (Polar Record, 1934)
I have read, with much interest, the article on the kayak and its construction and use, which appeared in the The Polar Record , No. 7, the more so since it revives for me old memories of more than twenty years ago. I know you will be interested to hear that the Swiss Trans-Greenland Expedition, led by the late A. de Quervain in 1912, made use of the kayak as often as possible. Six or seven members of the expedition practised the art, though more on the west coast than in the Angmagssalik district. The “juniors” Flick and Gaule had even taken with them from Switzerland their own kayaks, which had been made in Zurich, of canvas, and they had both learnt to turn over and right themselves, after the Greenland manner—on the lake at Zurich. The depôt left for de Quervain, for use on his arrival at the east coast of Greenland, contained four kayaks, with which to complete the journey to Angmagssalik, and in fact, he arrived there by kayak, having threaded his way through the ice-floes.